Pengaruh Budaya Organisasi dan Kepemimpinan terhadap Disiplin Kerja pada Pegawai Kantor Kecamatan Woja - Ferdiansyah Ferdiansyah; Irwansyah Irwansyah; Firmansyah Firmansyah (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This study aims to analyze the influence of organizational culture and leadership on work discipline in employees of the Woja District Office, both partially and simultaneously. Using a saturated sample, all employees in the agency were directly involved as respondents as many as 45 respondents. Primary data were collected through a structured questionnaire and analyzed using multiple linear regression analysis techniques. The results of the study showed that partially, organizational culture had a positive and significant effect on employee work discipline, while leadership did not have a significant influence independently. However, simultaneous testing proves that organizational culture and leadership together have a positive and significant influence on shaping employee work discipline. These findings indicate that although personal leadership style is not the primary determinant of discipline that has been bound by bureaucratic regulations, the synergy between internalizing strong work culture values and leadership support remains an important combination for an orderly work ecosystem. This research provides practical implications for government organizations in strengthening work culture, increasing leadership effectiveness, and creating a work environment that is able to encourage employee compliance, responsibility, and productivity in a sustainable manner.